Students' Perception on Blended Learning in English Listening and Speaking Class - Magdalena Kartikasari Tandy Rerung (Universitas Bunda Mulia, 2018)
Nowadays, the communicative teaching has been influenced by the development of technology. Becoming interactive teacher would not be enough if it is not supported by technology usage. Online learning in this case has been a powerful tool to help language learners during their learning progress. It is said that that online instruction raised the good and average student’s reading performance and the performance of the lowest-performing as well. In listening and speaking, online learning can help students improve their pronunciaton as well the comprehension skill. Therefore, the following study is designed to find out the students’ perceptions towards the use of both online and face-to-face learning in listening and speaking classroom. There are 30 students from the 1st and 3rd semester of English Language and Culture Departement and they joined the class for 1 semester. Online learning platform used was taken from Cambridge Learning Management System integrated with Unlock 2 and Unlock 4 books as the source of learning. The result shows that most of the students see online learning as an alternative tool to help them during their learning process.Keywords: blended learning, online learning, face-to-face learning, language learning